Strike dog : a Woods cop mystery - Heywood, Joseph (Heywood, Joseph. Woods cop mystery., 2007)
This Joseph Heywood mystery novel set in Michigan's Upper Peninsula finds Grady Service out to avenge the murder of his girlfriend and his son. Conservation officers in several states are being gruesomely slaughtered and Service, alone and devastated, navigates the mind of a serial killer before he becomes the next victim. Hunting the hunter through Wisconsin and Missouri, this is Heywood's most suspenseful and psychological thriller, perfect for fans of Thomas Perry, James Lee Burke or Nevada Barr. The fifth book in the series, STRIKE DOG is the perfect introduction to Heywood's fiction for outdoorsmen and animal lovers as well.